Zjawisko delokalizacji a rozszerzenie Unii Europejskiej - Odrobina, Anna (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2008)
Delocalization has to be seen against the background of a much wider process of structural changes caused by increasing globalization, international competition and technologie development. It is a phenomenon of totally or partially ceasing of the business activity and its reopening abroad. With the EU enlargement the core question of the "old" EU 15 countries is to observe the process of delocalization to new integrated countries with low costs of business activity. This article presents and analyses the European debate, policy options and challenges to the EU economy posed by delocalization. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2008; nr 1191, s. 394-405